2021
DOI: 10.7759/cureus.14914
|View full text |Cite
|
Sign up to set email alerts
|

CD117/c-KIT Expression in Phyllodes Tumor of the Breast and Its Correlation With Morphology and Clinical Outcome

Abstract: Introduction Breast phyllodes tumor’s (PT) clinical behavior is difficult to predict on histology. There is limited amount of data available on the role of biological markers. The objective of this study was to assess the expression of CD117 (c-KIT) in PT of the breast and its relationship with morphology and clinical outcome. Methods A total of 78 patients having available clinical records between 2004 and 2014 with breast PT were retrieved from the cancer registry at Shaukat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The formalin-fixed-paraffin embedded blocks were then sliced into 3-4 μm sections. Sliced sections were transferred onto L-lysin-treated slides, sequentially treated with xylene, alcohol, and water, and stained with hematoxylin and eosin [10]. These slides were examined by a senior histopathologist at the institute.…”
Section: Histological Sample Preparationmentioning
confidence: 99%
“…The formalin-fixed-paraffin embedded blocks were then sliced into 3-4 μm sections. Sliced sections were transferred onto L-lysin-treated slides, sequentially treated with xylene, alcohol, and water, and stained with hematoxylin and eosin [10]. These slides were examined by a senior histopathologist at the institute.…”
Section: Histological Sample Preparationmentioning
confidence: 99%
“…It has been shown in some studies that CD117 expression increases from benign to malignant PTs and that CD117 stromal-positive PTs tended to have a shorter recurrence-free survival. [30][31][32][33] Other studies, however, have shown no statistically significant differences between CD117 immunoreactivity and PT grades; [34][35][36] however, the number of investigations applying CD117 IHC to PTs in this context are few, the value of incorporating CD117 IHC in into the practice of grading PTs remains unclear.…”
Section: Attempts At Immunohistochemical Classificationmentioning
confidence: 99%